ANALISIS BACKDOOR LISTING DI INDONESIA PADA PERIODE 2009 HINGGA 2021 - Pandu Adi Cakranegara (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Backdoor Listing is a process for companies to enter the stock exchange. This process is still a rare practice in Indonesia. However, with the increasing number of technology companies that want to proliferate, the number of companies carrying out backdoor listings may increase in the future. This study aims to see the impact of the backdoor listing process, especially on investors. One indicator of the success of the backdoor listing is the increase in the company's value after the backdoor listing process. The method used in this study is mixed, namely qualitative methods and quantitative methods. Qualitative method using literature study. The existing literature, especially those that study backdoor listing that occurs in various countries. The quantitative method is seen by looking at the financial performance of companies that carry out backdoor listings. This study shows that companies that carry out backdoor listings experience an increase in value. In general, backdoor listings can create value for the company.